Crescentic glomerulonephritis: a possible complication of streptokinase treatment for myocardial infarction. Issue 5 (November 1986) - Murray, N; Lyons, J; Chappell, M
Abstract : Twenty days after a streptokinase infusion given for myocardial infarction, a patient developed a group G streptococcal throat infection. Thirteen days later he presented with a serum sickness type illness and progressive renal failure. Renal biopsy showed crescentic glomerulonephritis.